An Open Book: launching a library-based Open Access books hosting service - Wojturska, Rebecca (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
Edinburgh Diamond is a service situated within Edinburgh University Library that supports the publication of academic and student-led Diamond Open Access journals and books. This practice paper reviews the launch of our Open Access book hosting programme, and also our rebrand, looking at the timeline and challenges, and offering recommendations for those wishing to launch their own service.